Processing technology of recycled aggregate concrete

By adding silica to the impregnation liquid of the regenerated aggregate concrete, the problems of microcracks and large porosity of the regenerated aggregate are solved, and the strength and durability of the concrete are improved, making it more suitable for load-bearing components and structures.

CN119874274AInactive Publication Date: 2025-04-25JIANGSU VOCATIONAL INST OF ARCHITECTURAL TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510177006.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-18
Publication Date
2025-04-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The strength of existing recycled aggregate concrete is relatively low, which limits its application in load-bearing components and structures, mainly due to the microcracks and large porosity of the recycled aggregate itself.

Method used

By adding silica to the impregnation liquid, a strengthened impregnation liquid is formed, and the impregnation effect of the regenerated aggregate is improved through steps such as vacuum, pressure relief and drying, thereby enhancing its strength and durability.

Benefits of technology

It improves the compressive strength, flexural strength and durability of recycled aggregate concrete, so that it can better withstand external loads and deformations and extends its service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a processing technology of recycled aggregate concrete, and relates to the technical field of recycled aggregate concrete.The processing technology specifically comprises the following steps that recycled aggregate is crushed and screened; the preparation method comprises the following steps: dispersing cellulose fibers into a polyvinyl alcohol aqueous solution to obtain a basic reinforced impregnation liquid, adding silicon dioxide into the basic reinforced impregnation liquid, and fully stirring to uniformly disperse the silicon dioxide to form a reinforced impregnation liquid; placing the recycled aggregate in the reinforced impregnation liquid, and then vacuumizing to obtain reinforced recycled aggregate I; mixing the reinforced recycled aggregate I with part of polyvinyl alcohol fibers, spraying cement slurry onto the surface of the reinforced recycled aggregate I, and drying to obtain reinforced recycled aggregate II; and mixing the cement with the residual polyvinyl alcohol fiber, then adding water for mixing, and finally adding the reinforced recycled aggregate II and a water reducing agent to obtain the recycled aggregate concrete. By improving the impregnation liquid, the impregnation effect of the impregnation liquid on the recycled aggregate is improved, so that the mechanical property of the concrete is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of recycled aggregate concrete, and in particular to a processing technology of recycled aggregate concrete. Background Art

[0002] Recycled aggregate concrete is made by processing waste concrete blocks into recycled aggregate through crushing, screening, cleaning and other processes, and then mixing them into new concrete in a certain proportion. In this process, recycled aggregate replaces part or all of the natural aggregate, realizing the resource utilization of construction waste. However, the recycled aggregate particles prepared by simple crushing and screening processes are angular, rough on the surface, and contain hardened cement mortar. In addition, the concrete blocks accumulate damage in the crushing process, causing a large number of microcracks inside, resulting in the recycled aggregate itself having a large porosity, high water absorption, low bulk density, high void ratio, and high crushing index, which makes the strength of recycled aggregate concrete low, limiting its application in load-bearing components and structures.

[0003] For example, the Chinese patent with application number CN202110755101.X, a processing technology of recycled aggregate concrete, discloses a processing technology of recycled aggregate concrete, which relates to the technical field of recycled aggregate concrete, and includes the following steps: crushing and screening the recycled aggregate to obtain coarse and medium recycled aggregates respectively; dispersing cellulose fibers in a polyvinyl alcohol aqueous solution to obtain a reinforced impregnation liquid; placing the coarse and medium recycled aggregates in the reinforced impregnation liquid, evacuating, then depressurizing and evacuating again, filtering, washing, and drying to obtain reinforced recycled aggregate I; mixing reinforced recycled aggregate I and part of the polyvinyl alcohol fibers, stirring, spraying cement slurry on its surface, and drying to obtain reinforced recycled aggregate II; mixing cement and the remaining polyvinyl alcohol fibers, stirring, then adding water to mix, and finally adding reinforced recycled aggregate II and a water reducer to obtain recycled aggregate concrete. The recycled concrete prepared by the invention has high mechanical properties, and its compressive strength is greater than or equal to 8.43MPa, and its splitting tensile strength is above 1.95MPa.

[0004] The above technical solution improves the strength of the recycled aggregate to a certain extent, but the strength improvement of the recycled aggregate by chemically strengthening the recycled aggregate through the strengthening impregnation liquid is limited. Summary of the invention

[0005] The embodiment of the present application provides a processing technology for recycled aggregate concrete, thereby solving the problem in the prior art that the recycled aggregate itself has microcracks and pores, which affect the strength and durability of the concrete. By further improving the impregnation liquid, the impregnation effect of the recycled aggregate is improved, thereby improving the mechanical properties of the concrete.

[0006] The present invention provides a processing technology for recycled aggregate concrete, which specifically includes the following steps: S1, crushing and screening the recycled aggregate to obtain coarse and medium recycled aggregates respectively; S2, dispersing the cellulose fibers in a polyvinyl alcohol aqueous solution to obtain a basic strengthening impregnation solution, adding silicon dioxide to the basic strengthening impregnation solution, and stirring the silicon dioxide to uniformly disperse the silicon dioxide to form a strengthening impregnation solution; S3, placing the coarse and medium recycled aggregates in the strengthening impregnation liquid, stirring until the mixture is uniform, then vacuuming, controlling the pressure to -0.085~-0.095MPa within 30-40min, maintaining for 45-60min, then releasing the pressure to normal pressure, vacuuming again, controlling the pressure to -0.085~-0.095MPa within 30-40min, maintaining for 45-60min, filtering, washing, and drying to obtain the strengthened recycled aggregate I; S4, mixing the reinforced recycled aggregate I and part of the polyvinyl alcohol fiber, stirring, spraying cement slurry on the surface thereof, and drying to obtain reinforced recycled aggregate II; S5. Mix the cement and the remaining polyvinyl alcohol fibers, stir, then add water and mix, and finally add the reinforced recycled aggregate II and the water reducing agent to obtain the recycled aggregate concrete.

[0007] Furthermore, the mass ratio of cellulose fiber to polyvinyl alcohol in S2 is 1-3:10; the mass percentage concentration of polyvinyl alcohol aqueous solution is 0.5%-2%; the particle size of silicon dioxide is 10-100nm; and the mass of silicon dioxide is 5%-8% of the total mass of the basic strengthening impregnation solution.

[0008] Furthermore, the material-liquid ratio of the S3 medium coarse and medium recycled aggregate to the enhanced impregnation liquid is 1:22-28.

[0009] Furthermore, the silicon dioxide also includes different particle sizes, with a large particle size of 10-50 μm and a small particle size of 10-100 nm.

[0010] Furthermore, the mass ratio of the large-particle size and small-particle size silicon dioxide is 3-5:2-3.

[0011] Furthermore, in step S2, the silicon dioxide is pretreated before being added to the basic impregnation solution.

[0012] Furthermore, the pretreatment is specifically to add silicon dioxide of different particle sizes into a hydrochloric acid solution respectively, stir evenly, and perform etching.

[0013] Furthermore, the concentration of the hydrochloric acid solution is 37%.

[0014] Furthermore, the volume of the hydrochloric acid solution is 2-3 times the volume of the large-particle silicon dioxide, and etching is performed at room temperature for 24 hours.

[0015] Furthermore, the volume of the hydrochloric acid solution is 1-1.5 times the volume of the small-particle silicon dioxide, and etching is performed at room temperature for 10 hours.

[0016] One or more technical solutions provided in the embodiments of the present application have at least the following technical effects or advantages: First, the silica particles have a large specific surface area and can be adsorbed on cellulose fibers and polyvinyl alcohol molecular chains, forming a stable dispersion system through physical forces such as van der Waals forces and hydrogen bonds, promoting the uniform dispersion of silica particles in the impregnation liquid and preventing them from agglomerating and precipitating; the hydroxyl groups on the surface of silica react with the hydroxyl groups on cellulose fibers or polyvinyl alcohol molecular chains to form chemical bonds; the binding force between silica and cellulose fibers and polyvinyl alcohol is enhanced, and the stability and performance of the impregnation liquid are improved; the addition of silica fills the gaps between cellulose fibers and polyvinyl alcohol molecular chains, forming a denser network structure, enhancing the strength and toughness of the impregnation liquid, and improving its impregnation effect on recycled aggregates; silica particles can penetrate into the microcracks and pores of recycled aggregates, and together with cellulose fibers and polyvinyl alcohol form a dense impregnation layer, thereby improving the strength and durability of the recycled aggregates and reducing their breakage and aging during use; Secondly, large-size silica provides initial support and protection, while small-size silica penetrates into the internal structure of aggregate to fill and strengthen, forming a composite filling method. The composite filling method can make full use of the advantages of silica of different particle sizes, and improve its mechanical properties and durability by optimizing the microstructure of aggregate; large-size silica particles can fill the larger pores in the recycled aggregate, provide support and skeleton effect, and enhance the overall structural stability of the aggregate, while small-size silica particles can penetrate into the tiny cracks and pores of the recycled aggregate, tightly bond with the surface of the aggregate, and form a denser microstructure; silica particles of different particle sizes form a multi-level, multi-scale rough structure on the surface of the recycled aggregate, increase the contact area and bonding force between the aggregate and the cement matrix, and improve the compressive strength and flexural strength of the recycled aggregate concrete, thereby improving the overall mechanical properties of the concrete; the synergistic effect of large and small-size silica makes the microstructure of the recycled aggregate concrete more uniform and dense, reduces the porosity and permeability of the concrete, and improves the mechanical properties of the concrete; Third, there are a large number of hydroxyl groups and other active groups on the surface of silica particles, which can react with hydrogen ions in hydrochloric acid solution, causing the silica surface to be etched; silica particles of different particle sizes have different reaction speeds and degrees to etching due to their different surface areas and porosities; during pretreatment, through etching, large-particle silica will remove more surface substances, expose more active sites, increase surface roughness and specific surface area, while small-particle silica mainly removes surface impurities and weakly bound substances, maintains the integrity of the particles, and increases a certain degree of roughness and activity. DETAILED DESCRIPTION

[0017] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which the present invention belongs; the terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention; the term "and / or" used herein includes any and all combinations of one or more related listed items.

[0018] Embodiment 1: A processing technology for recycled aggregate concrete, specifically comprising the following steps: S1, crushing and screening the recycled aggregate to obtain coarse and medium recycled aggregates respectively; Among them, the particle sizes of coarse and medium recycled aggregates are 7.5-12mm and 4.75-7.5mm respectively, and their mass ratio is 30-40:30-40; S2, dispersing the cellulose fibers in a polyvinyl alcohol aqueous solution to obtain a basic strengthening impregnation solution, adding silicon dioxide to the basic strengthening impregnation solution, and stirring the silicon dioxide to uniformly disperse the silicon dioxide to form a strengthening impregnation solution; The mass ratio of cellulose fiber to polyvinyl alcohol is 1-3:10; the mass percentage concentration of polyvinyl alcohol aqueous solution is 0.5%-2%; the particle size of silicon dioxide is 10-100nm; the mass of silicon dioxide is 5%-8% of the total mass of the basic strengthening impregnation solution; S3, placing the coarse and medium recycled aggregates in the strengthening impregnation liquid, stirring until the mixture is uniform, then vacuuming, controlling the pressure to -0.085~-0.095MPa within 30-40min, maintaining for 45-60min, then releasing the pressure to normal pressure, vacuuming again, controlling the pressure to -0.085~-0.095MPa within 30-40min, maintaining for 45-60min, filtering, washing, and drying to obtain the strengthened recycled aggregate I; Among them, the material-liquid ratio of coarse and medium recycled aggregates to enhanced impregnation liquid is 1:22-28; S4, mixing the reinforced recycled aggregate I and part of the polyvinyl alcohol fiber, stirring, spraying cement slurry on the surface thereof, and drying to obtain reinforced recycled aggregate II; The amount of polyvinyl alcohol fiber added to each cubic meter of concrete mortar is 0.9-1.2 kg / m³; the mass percentage of polyvinyl alcohol fiber is 15-25:75-85; the mass volume ratio of reinforced recycled aggregate I to cement mortar is kg / m³1.5×10 4 ~2.0×10 4 :1; the water-cement ratio of cement mortar is 0.8:1; S5. Mix the cement and the remaining polyvinyl alcohol fibers, stir, then add water and mix, and finally add the reinforced recycled aggregate II and the water reducing agent to obtain the recycled aggregate concrete.

[0019] The mass percentage of the polyvinyl alcohol fiber is 15-25:75-85.

[0020] Experiments were conducted for this embodiment. Specifically, Experiment 1: The mass ratio of S1, coarse and medium recycled aggregates is 30:30; The mass ratio of S2, cellulose fiber and polyvinyl alcohol is 1:10, the mass percentage concentration of polyvinyl alcohol aqueous solution is 0.5%, the particle size of silicon dioxide is 10-100nm; the mass of silicon dioxide is 5% of the total mass of the basic strengthening impregnation solution; S3, the material-liquid ratio of coarse and medium recycled aggregate to enhanced impregnation liquid is 1:22; S4. The amount of polyvinyl alcohol fiber added per cubic meter of concrete mortar is 0.9 kg / m 3 In S4 and S5, the mass percentage of polyvinyl alcohol fiber is 15:85; the mass volume ratio of reinforced recycled aggregate I and cement mortar is kg / m 3 1.5×10 4: 1; The water-cement ratio of cement mortar is 0.8:1; Experiment 2: The mass ratio of S1, coarse and medium recycled aggregates is 30:35; The mass ratio of S2, cellulose fiber and polyvinyl alcohol is 1.5:10, the mass percentage concentration of polyvinyl alcohol aqueous solution is 1%, the particle size of silicon dioxide is 10-100nm; the mass of silicon dioxide is 8% of the total mass of the basic strengthening impregnation solution; S3, the material-liquid ratio of coarse and medium recycled aggregate to enhanced impregnation liquid is 1:24; S4. The amount of polyvinyl alcohol fiber added per cubic meter of concrete mortar is 1.0 kg / m 3 In S4 and S5, the mass percentage of polyvinyl alcohol fiber is 20:80; the mass volume ratio of reinforced recycled aggregate I and cement mortar is kg / m 3 1.7×10 4: 1; The water-cement ratio of cement mortar is 0.8:1; Experiment 3: S1, the mass ratio of coarse to medium recycled aggregate is 30:40; The mass ratio of S2, cellulose fiber and polyvinyl alcohol is 2:10, the mass percentage concentration of polyvinyl alcohol aqueous solution is 1.5%, the particle size of silicon dioxide is 10-100nm; the mass of silicon dioxide is 6.5% of the total mass of the basic strengthening impregnation solution; S3, the material-liquid ratio of coarse and medium recycled aggregate to enhanced impregnation liquid is 1:27; S4. The amount of polyvinyl alcohol fiber added per cubic meter of concrete mortar is 1.1 kg / m 3 In S4 and S5, the mass percentage of polyvinyl alcohol fiber is 20:80; the mass volume ratio of reinforced recycled aggregate I and cement mortar is kg / m 3 1.8×10 4: 1; The water-cement ratio of cement mortar is 0.8:1; The comparative example uses the method with application number CN202110755101.X to prepare recycled aggregate concrete, which differs from the present embodiment in that the enhanced impregnation liquid does not contain silicon dioxide; The properties of the recycled aggregate concrete prepared in Experiments 1-3 of Example 1 of the present invention and the comparative example were tested.

[0021] Testing method: The specimens were mixed with a SJD60 forced concrete mixer, loaded and vibrated twice, demolded after 1 day of molding, and sent to the curing room for standard curing for 28 days. The specimen size is 100mm×100mm×100mm, with 6 pieces in each group. The average value was taken as the measured value of the index to be tested for this group of specimens during the test. The compressive strength and splitting tensile strength were carried out in accordance with the "Standard for Test Methods of Mechanical Properties of Ordinary Concrete" (GB / T50081-2002), and the test instrument was WAW-600C universal testing machine.

[0022] The specific test results are shown in the table below:

[0023] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages: The silica particles have a large specific surface area and can be adsorbed on the cellulose fibers and polyvinyl alcohol molecular chains, forming a stable dispersion system through physical forces such as van der Waals forces and hydrogen bonds, promoting the uniform dispersion of the silica particles in the impregnation liquid and preventing them from agglomerating and precipitating; the hydroxyl groups on the surface of silica react with the hydroxyl groups on the cellulose fibers or polyvinyl alcohol molecular chains to form chemical bonds; the binding force between silica and the cellulose fibers and polyvinyl alcohol is enhanced, and the stability and performance of the impregnation liquid are improved; the addition of silica fills the gaps between the cellulose fibers and the polyvinyl alcohol molecular chains, forming a denser network structure, enhancing the strength and toughness of the impregnation liquid, and improving its impregnation effect on the recycled aggregate; the silica particles can penetrate into the microcracks and pores of the recycled aggregate, and together with the cellulose fibers and polyvinyl alcohol form a dense impregnation layer, thereby improving the strength and durability of the recycled aggregate and reducing its breakage and aging during use; The addition of silica improves the surface properties of recycled aggregate and improves its bonding with the cement matrix, thereby enhancing the compressive strength, flexural strength and durability of recycled aggregate concrete, enabling recycled aggregate concrete to better withstand external loads and deformations, extending its service life and improving the overall performance of recycled aggregate concrete; silica particles form a more uniform and dense microstructure in the concrete, reducing the porosity and permeability of the concrete and improving the mechanical properties of the concrete.

[0024] Example 2: In the above-mentioned Example 1, silicon dioxide is added to the impregnating liquid. The silicon dioxide reacts with the cellulose fibers and polyvinyl alcohol to form a denser network structure, thereby enhancing the impregnation effect, improving the strength and durability of the recycled aggregate, and thus improving the overall performance of the concrete. In order to further improve the overall performance of the concrete, further improvements are made on the basis of Example 1.

[0025] The silicon dioxide also includes different particle sizes, the large particle size is 10-50 μm, the small particle size is 10-100 nm, and the mass ratio of the large particle size to the small particle size silicon dioxide is 3-5:2-3.

[0026] This embodiment is based on Experiment 3 of Example 1. The difference from Experiment 3 of Example 1 is that the silicon dioxide has different particle sizes, the large particle size is 10-50 μm, the small particle size is 10-100 nm, and the mass ratio of the large particle size to the small particle size silicon dioxide is 4:2.5. After testing, the compressive strength of the recycled aggregate concrete in this embodiment is 11.83 MPa, and the splitting tensile strength is 2.7 MPa.

[0027] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages: Large-sized silica provides initial support and protection, while small-sized silica penetrates into the internal structure of the aggregate to fill and strengthen it, forming a composite filling method. The composite filling method can make full use of the advantages of silica of different particle sizes and improve its mechanical properties and durability by optimizing the microstructure of the aggregate. Large-sized silica particles can fill the larger pores in the recycled aggregate, provide support and skeleton functions, and enhance the overall structural stability of the aggregate. Small-sized silica particles can penetrate into the tiny cracks and pores of the recycled aggregate, tightly bond with the aggregate surface, and form a denser microstructure. Silica particles of different particle sizes form a multi-level, multi-scale rough structure on the surface of the recycled aggregate, increasing the contact area and bonding force between the aggregate and the cement matrix, improving the compressive strength and flexural strength of the recycled aggregate concrete, and thus improving the overall mechanical properties of the concrete. The synergistic effect of large and small-sized silica particles makes the microstructure of the recycled aggregate concrete more uniform and dense, reduces the porosity and permeability of the concrete, and improves the mechanical properties of the concrete. The composite filling method of silica with different particle sizes improves the strength and durability of recycled aggregate, enables it to be better used in concrete, optimizes the microstructure of concrete, improves its mechanical properties and durability, enables it to better withstand external loads and deformations, and improves the overall performance of concrete.

[0028] Embodiment 3: Embodiment 2 above improves the strength and durability of recycled aggregate by introducing silica particles of different particle sizes and utilizing the filling and strengthening effects of silica of different particle sizes. In order to further improve the overall performance of concrete, further improvements are made on the basis of Embodiment 2.

[0029] In step S2, the silicon dioxide is also pre-treated before being added to the base impregnation solution, specifically, Add silicon dioxide of different particle sizes into the hydrochloric acid solution respectively, stir evenly, and perform etching; The concentration of the hydrochloric acid solution is 37%, the volume of the hydrochloric acid solution is 2-3 times the volume of the large-particle silica, and the etching is carried out at room temperature for 24 hours; the volume of the hydrochloric acid solution is 1-1.5 times the volume of the small-particle silica, and the etching is carried out at room temperature for 10 hours.

[0030] This embodiment is experimented on the basis of the experiment of the second embodiment. The difference from the experiment of the second embodiment is that the silicon dioxide is pretreated before being added to the basic impregnation solution. The large-particle silicon dioxide is added to the 37% hydrochloric acid solution, stirred evenly, the volume of the hydrochloric acid solution is 2.5 times the volume of the large-particle silicon dioxide, and etched at room temperature for 24 hours; the small-particle silicon dioxide is added to the 37% hydrochloric acid solution, stirred evenly, the volume of the hydrochloric acid solution is 1.2 times the volume of the small-particle silicon dioxide, and etched at room temperature for 10 hours; After testing, the compressive strength of the recycled aggregate concrete in this embodiment is 12.33 MPa, and the splitting tensile strength is 2.8 MPa.

[0031] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages: There are a large number of hydroxyl groups and other active groups on the surface of silica particles, which can react with hydrogen ions in hydrochloric acid solution, resulting in etching of the silica surface. Due to the difference in surface area and porosity, silica particles of different particle sizes have different reaction speeds and degrees to etching. During pretreatment, through etching, large-particle silica will remove more surface substances, expose more active sites, and increase surface roughness and specific surface area, while small-particle silica mainly removes impurities and weakly bound substances on the surface, maintains the integrity of the particles, and increases a certain degree of roughness and activity. The surface of the etched silica particles is rougher and the specific surface area is increased, which increases the contact area and physical adsorption force with the cellulose fiber, polyvinyl alcohol and the surface of the recycled aggregate. At the same time, the active groups such as hydroxyl groups generated during the etching process can form chemical bonds with the matrix material to further enhance the bonding force. The etching degree of large-particle silica is deeper, which enables it to better fill the larger pores in the recycled aggregate and provide stronger support. The shallower etching of small-particle silica maintains its ability to fill tiny cracks and pores, while increasing the bonding strength with the aggregate surface. This composite filling method further optimizes the microstructure of the recycled aggregate and improves its mechanical properties and durability.

[0032] Due to the enhanced bonding between the etched silica particles and the matrix material, the stability and durability of the recycled aggregate in the concrete are improved, the pores and cracks inside the concrete are reduced, and the concrete's impermeability, frost resistance and corrosion resistance are improved. At the same time, due to the increased strength of the recycled aggregate, the mechanical properties of the entire concrete are also improved, and it can better withstand external loads and deformations.

[0033] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A processing technology for recycled aggregate concrete, characterized in that: The specific steps include: S1, crushing and screening the recycled aggregate to obtain coarse and medium recycled aggregates respectively; S2, dispersing the cellulose fibers in a polyvinyl alcohol aqueous solution to obtain a basic strengthening impregnation solution, adding silicon dioxide to the basic strengthening impregnation solution, and stirring the silicon dioxide to uniformly disperse the silicon dioxide to form a strengthening impregnation solution; S3, placing the coarse and medium recycled aggregates in the strengthening impregnation liquid, stirring until the mixture is uniform, then vacuuming, controlling the pressure to -0.085~-0.095MPa within 30-40min, maintaining for 45-60min, then releasing the pressure to normal pressure, vacuuming again, controlling the pressure to -0.085~-0.095MPa within 30-40min, maintaining for 45-60min, filtering, washing, and drying to obtain the strengthened recycled aggregate I; S4, mixing the reinforced recycled aggregate I and part of the polyvinyl alcohol fiber, stirring, spraying cement slurry on the surface thereof, and drying to obtain reinforced recycled aggregate II; S5. Mix the cement and the remaining polyvinyl alcohol fibers, stir, then add water and mix, and finally add the reinforced recycled aggregate II and the water reducing agent to obtain the recycled aggregate concrete.

2. The processing technology of recycled aggregate concrete according to claim 1, characterized in that: The mass ratio of cellulose fiber to polyvinyl alcohol in S2 is 1-3:10; the mass percentage concentration of polyvinyl alcohol aqueous solution is 0.5%-2%; the particle size of silicon dioxide is 10-100nm; the mass of silicon dioxide is 5%-8% of the total mass of the basic strengthening impregnation solution.

3. The processing technology of recycled aggregate concrete according to claim 1, characterized in that: The material-liquid ratio of S3 medium coarse and medium recycled aggregate to the enhanced impregnation liquid is 1:22-28.

4. The processing technology of recycled aggregate concrete according to claim 2, characterized in that: The silicon dioxide also includes different particle sizes, with a large particle size of 10-50 μm and a small particle size of 10-100 nm.

5. The processing technology of recycled aggregate concrete according to claim 4, characterized in that: The mass ratio of the large-particle size and small-particle size silicon dioxide is 3-5:2-3.

6. The processing technology of recycled aggregate concrete according to claim 4, characterized in that: In step S2, the silicon dioxide is also pretreated before being added to the basic impregnation solution.

7. The processing technology of recycled aggregate concrete according to claim 6, characterized in that: The pretreatment specifically includes adding silicon dioxide of different particle sizes into a hydrochloric acid solution respectively, stirring evenly, and etching.

8. The processing technology of recycled aggregate concrete according to claim 7, characterized in that: The concentration of the hydrochloric acid solution is 37%.

9. The processing technology of recycled aggregate concrete according to claim 8, characterized in that: The volume of the hydrochloric acid solution is 2-3 times the volume of the large-particle silicon dioxide, and etching is performed at room temperature for 24 hours.

10. The processing technology of recycled aggregate concrete according to claim 8, characterized in that: The volume of the hydrochloric acid solution is 1-1.5 times the volume of the small-particle silicon dioxide, and etching is performed at room temperature for 10 hours.

Citation Information

Patent Citations

  • A processing technology for recycled aggregate concrete

    CN113354350B